SMART BRACELETS-THE BREADTH OF OUR NEED FOR MODERN DEVICES THAT MONITOR THE HEALTH OF YOUNG CHILDREN AND BABIES IN REAL TIME. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
: In today's fast-paced world, ensuring the health and safety of young children and babies is a top priority for parents. Smart bracelets, equipped with real-time monitoring features, have emerged as an essential tool for tracking vital signs such as heart rate, temperature, oxygen levels, and sleep patterns. These modern devices provide instant alerts in case of abnormalities, helping caregivers respond promptly to potential health risks. This article explores the growing need for smart health monitoring devices, their benefits, and their role in revolutionizing child healthcare and parental peace of mind.